Kerja lapangan dan simulasi peradilan sebagai metode pembelajaran mata kuliah Hukum Administrasi Negara - Eny Kusdarini; Setiati Widihastuti (Universitas Negeri Yogyakarta, 2010)
The recent lecture practices tend to produce the alumnus having the cognitive-oriented of subject mastery. Moreover the paradigm of teacher centered learning is still applied in the learning which positioned the teacher as its central figure. Based on the explanation above, this research has an objective to develop the field work method and the fictive justice functioned as the learning model of State Administration Law subject in Department of Civic Education and Law (PKnH) FISE UNY which applies student centered learning characteristic. It is a qualitative and descriptive research. The object of this research is the learning model using the field work method and role playing in the State Administration Court material. The subject of this research is the whole 6th term students of PKnH taking the State Administration Law subject 2008-2009. The data are collected by using observation, documentation, and interview. The data are analyzed inductively, started by the data collection and ended in the data conclusion and verification. The result shows that: 1) the substance of the State Administration Law subject material can be used in developing the civil knowledge about the duty-right and the role of being a good citizen; 2) the civic skills; intellectual and participation skill can be developed by the exploration of the field work and fictive justice method; 3) the field work and fictive justice method is quite significant in realizing the active, interactive, and contextual learning process based on the student centered learning.